The Relationship Between Maternal Mental Health and Estimated Fetal Weight (EFW) in Second- and Third-Trimester Pregnant Women - Inggrid Wuri Wulansari; Ervin Rufaindah; Dwi Norma Retnaningrum (Media Husada Journal of Midwifery Science, 2026)
Maternal mental health during pregnancy is a crucial factor affecting both maternal and fetal well-being, including the estimated fetal weight (EFW). Unaddressed mental health issues such as stress, anxiety, and depression can increase the risk of fetal growth restriction and preterm birth. This study aimed to determine the relationship between maternal mental health and EFW in second and third trimester pregnant women at the Maternity Clinic of Dr. Saiful Anwar General Hospital Malang. This study employed a quantitative method with a cross-sectional design. The study population consisted of all second and third trimester pregnant women who had antenatal check-ups at the maternity clinic. A non-probability purposive sampling technique was used, resulting in a total of 34 respondents. The instrument used to measure mental health was the Mental Health Continuum–Short Form (MHC-SF), and the Hadlock chart was used to estimate EFW based on ultrasonographic measurements. Data were analyzed using the Spearman rank correlation test. The results shows that most respondents has flourishing mental health and most EFWs are in the normal category. Based on statistical analysis, a significant relationship is found between maternal mental health and EFW (p-value < 0.05). It can be concluded that there is a relationship between maternal mental health and EFW in second and third trimester pregnant women. Health workers are advised to pay greater attention to the psychological condition of pregnant women during antenatal care to prevent fetal complications.